2015
DOI: 10.1021/acsami.5b07372
|View full text |Cite
|
Sign up to set email alerts
|

Prototype Development of the Intelligent Hydrogel Wound Dressing and Its Efficacy in the Detection of Model Pathogenic Wound Biofilms

Abstract: The early detection of wound infection in situ can dramatically improve patient care pathways and clinical outcomes. There is increasing evidence that within an infected wound the main bacterial mode of living is a biofilm: a confluent community of adherent bacteria encased in an extracellular polymeric matrix. Here we have reported the development of a prototype wound dressing, which switches on a fluorescent color when in contact with pathogenic wound biofilms. The dressing is made of a hydrated agarose film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 38 publications
(78 reference statements)
1
108
0
Order By: Relevance
“…Therefore, it is very important to have the antibacterial surface directly on the bandage to avoid the formation of these bacteria films, preventing bacteria multiplication inside the bandage [5]. Bacterial infections are usually treated with antibiotics; however, a good effect is not obtained in every case, and this is because many bacteria are immunized to antibiotics after being subjected to the treatment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to have the antibacterial surface directly on the bandage to avoid the formation of these bacteria films, preventing bacteria multiplication inside the bandage [5]. Bacterial infections are usually treated with antibiotics; however, a good effect is not obtained in every case, and this is because many bacteria are immunized to antibiotics after being subjected to the treatment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide NPs have been reported to have a high affinity for macrophages (4850). Hence, these NPs, specifically the subset with diameters <50 nm known as ultrasmall superparamagnetic iron oxide nanoparticles (USPIOs), have been used as agents to aid imaging of AAAs in both animal models and patients (3035). USPIOs such as ferumoxytol are composed of an iron oxide core enclosed by a hydrophilic coating that readily accrues in neutrophils and macrophages (51).…”
Section: Aaa Pathogenesis and Potential Imaging Targets For Npsmentioning
confidence: 99%
“…Both animal and human studies have suggested that NPs, particularly those with an iron oxide component, can be taken up by AAAs and identified on imaging (3035). We highlight some of these studies in the following sections.…”
Section: Studies Assessing Nps In Aaa Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the self-healing endows the material more than one life. There is much potential relevance of selfhealing hydrogels in the fields of biosensors, wound dressing, shape memory material and biomedical carrier [9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%